Antituberculosis and Toxicity Assay of ethanolic extract of Mimba Cortex (Azadirachta indica JUSS.) - Cut Fatimah; Erfan Wahyudi; Ernawati B. (Indonesian Journal of Cancer Chemoprevention, 2015)
According to WHO has identified so much people with tuberculosis disorder, and includes a disease that causes death. Mycobacterium tuberculosis has been resistant to antituberculosis drugs were used, while the discovery of new synthetic antituberculosis are very slow. Traditionally, mimba cortex has been used to treat cough and bloody sputum. In previous research proved that the ethanol extract of mimba cortex can inhibit the in vitro growth of Mycobacterium tuberculosis. This study was conducted to determine the potential of mimba cortex as antituberculosis in vivo and toxicity test. Antituberculosis potency test in vivo in guinea pigs infected with Mycobacterium tuberculosis H37Rv directly into the bronchi using nebulizer. Then given mimba cortex extract 3 times a day 100 mg/kgBW and 50 mg/kgBW. Isoniazid, Rifampicin and Ethambutol used as a comparison. Antituberculosis assessment examination conducted by Mycobacterium tuberculosis on bronchial fluid speciments were taken every two weeks and tested in culture with Lowenstein-Jensen method. Acute toxicity test conducted on mice, the LD50 value calculation and observation of liver, kidney, and lung histopathology. The result of research showed that the ethanol extract of mimba cortex have antituberculosis activity in guinea pigs which has infected with Mycobacterium tuberculosis H37Rv, 3 times daily dosing of 100 mg/kgBW for 6 weeks, showed that bacterium from +3 to negative, and 3 times daily dosing of 50mg/kgBW showed that bacterium from +3 to +1. Acute toxicity test results showed LD50 11.85 ± 0.571. That is including mild toxic category.Keywords: mimba cortex, antituberculosis activity, acute toxicity